EXPERIENCE OF RECONSTRUCTIVE-REHABILITATED SURGICAL INJURIES IN PATIENTS WITH STOMAS AFTER GUNSHOT WOUNDS OF THE ABDOMEN - Verba А.V.; Zheliba, M.D.; Bogush, G.L.; Halushka А.М.; Dovgan, I.I. (World of Medicine and Biology, 2019)
The purpose of the work was to study the character of modern abdominal combat injuries and to share the experience of the rehabilitation and restorative surgical interventions in patients with stomas. Analysis of the medical documents of 15 patients injured in abdomen, who were imposed by a discharged stoma, was conducted. After eliminating life threat, reconstructive surgical interventions, which consisted in elimination of stoma and imposition of different types of colonic anastomoses, were performed. 7 patients have complications in the postoperative period, such as acute ulcers of the upper gastrointestinal tract in 2 cases, external fistula of small intestine in 1 case, acute adhesive obstruction in 1 case and suppuration of the wound in 5 cases. The obtained results reveal severity of thwe modern abdominal warfare injury and complexity of the reconstructive-restoration operations in patients with numerous postoperative complications.